Enzymatic hydrolysis of carbohydrates in by-products of processed rice - Turini,Camila da Silva (2021)
ABSTRACT: Over post-harvest steps of rice, from pre-cleaning to processing, a large amount of by-product is generated. Some of these by-products, due to their high starch and fiber content can be used in ethanol production. The objective was to evaluate the effect of enzymatic hydrolysis conditions on the production of reducing sugars, from pre-cleaning residue and type III paddy rice, as well as the effect of the pre-treatment of its fibers, targeting the use of these residues in ethanol fuel production. The proximate analysis was performed, followed by the pre-treatment of samples. Enzymatic hydrolysis was conducted in two ways: using one enzyme at a time or applying them simultaneously. The starch content was 41.18 and 53.41%; the fibers were 30.44 and 23.39%, of which 6.53 and 4.41% were lignin, for the pre-cleaning residue and paddy rice, respectively. Alkaline pre-treatment reduce lignin content by 47.94 and 18.23% for the pre-cleaning residue and type III paddy rice, respectively. Hydrolysis efficiency was 22.61 and 15.32% for the cellulase enzyme, and 82.18 and 87.07% for the amylolytic enzymes in the pre-cleaning residue and type III paddy rice, respectively. The hydrolysis with the separated enzymes presented higher reducing sugar yields. Therefore, the pre-cleaning residue and type III paddy rice can be used for ethanol production by its enzymatic hydrolysis, aiming to add value and to increase the sustainability of the rice production chain.